Earlier antiretroviral initiation is independently associated with better arterial stiffness in children living with perinatally acquired HIV with sustained viral suppression in Mozambique - Igor S. Dobe; Ana O. Mocumbi; Noorjean Majid; Birhanu Ayele; Sara H. Browne; Steve Innes (AOSIS, 2021)
Background: Cardiovascular disease is a major driver of morbidity and mortality in adults living with HIV. The drivers of cardiovascular disease in children living with perinatally acquired HIV (PHIV) with sustained HIV viral suppression are unclear. Objectives: We explored the contribution of HIV-specific risk factors to arterial stiffness independently of traditional risk factors (metabolic syndrome [MetS]) in prepubertal children with PHIV with sustained viral suppression in a low-income country in Africa. Method: For this cross-sectional analysis, arterial stiffness was assessed by pulse wave velocity z-score (PWVz), measured using a Vicorder device. Metabolic syndrome components were measured. We retrospectively collected the antiretroviral therapy (ART) exposures, HIV stage, CD4 count and HIV viral load. A multivariate linear regression model was constructed for MetS components, retaining age and gender as obligatory variables. We then added HIV-related metrics to assess whether these had an independent or additive effect. Results: We studied 77 virally suppressed children with PHIV without evidence of cardiovascular disease (from medical history and physical examination). In the initial model, the PWVz was independently associated with each MetS component. The PWVz was higher in participants with proportionally greater visceral fat (waist/height ratio), elevated lipids (triglyceride/high-density lipoprotein ratio) and insulin resistance (log homeostatic model assessment [HOMA]). The addition of age at ART initiation increased the model R2 value from 0.36 to 0.43. In the resulting model, younger age at ART initiation was independently associated with a better PWVz (P 0.001). Conclusion: Earlier ART initiation was independently associated with lower large artery stiffness. This effect was independent of the effect of elevated lipids, visceral fat and insulin resistance.